Experimental activities in science teaching of children with special educational needs in preschool - Reis, Carlos (2014)
The study developed fits science education area, designated in Portuguese Preschool Education by Environment Knowledge. In particular, we explored the theme of physical states of water. We build learning pathways by using practical-experimental activities as methodology. The problem of this research study is to understand whether the practices and experimental activities in science contribute to learning of children with special educational needs. As methodology we applied research-action to work with a group of children, aged 4 years, of a kindergarten in Guarda, a small town of Beira Interior, Portugal. The referred group included a child with permanent Special Educational Needs regarding motor and speech competences. We can conclude that, in the course of practice and experimental activities, children with special educational needs showed a similar involvement of other children in the group and at the end of such activities, they presented significant learning achievements. It was also verified that the use of practical and experimental activities for science teaching in preschool education are an excellent means of inclusion of children with special educational needs. This template will assist you in formatting your paper.